Pengaruh Profitabilitas, Likuiditas, Leverage, Aktivitas, Pertumbuhann Penjualan Terhadap Financial Distress Perusahaan Kimia - Imam Asfali (Program Pascasarjana Universitas Gajayana, 2019)
This Study aims to identify and analyze the influence of Profitability, Liquidity, Leverage, Activity, and sale growth to financial distress at the company’s Chemical Industry in the Indonesia Stock Exchange (BEI). The sample used in this study was 8 (eight) Chemical Industry companies listed on the Stock Exchange. The analytical method used is descriptive statistical methods and multiple linier regression. The result showed that return on asset, Current Ratio, Debt to Total Assets Total Asset Turnover, and sales growth have positive and significant impact on financial distress. Partially current ratio positive and significant impact on the financial distress in the Chemical Industry companies listed on the Indonesian Stock Exchange (BEI) and while the debt ratio and significant positive effect on the financial distress in the Chemical Industry companies listed on the Indonesian Stock Exchange (BEI), while ROA (return on asset) variable influence positively and significant on the financial distress in the Chemical Industry companies listed on the Indonesian Stock Exchange (BEI) and sales growth have positive and insignificant effect on the financial distress in the Chemical Industry companies listed on the Indonesian Stock Exchange (BEI).